Vertebral fracture and spinal cord compression after removal of pedicle screws in PD patients: case report and literature review - Wen, Jingchao; Su, Yingfeng; Guo, Jiandong; Fan, Shunwu; Fang, Xiangqian; Chen, Junxin; Xu, Wenbin (Frontiers in Surgery, 2025)
IntroductionPedicle screws are used in spinal surgery and have yielded favorable postoperative outcomes. Despite this, the optimal timing for their removal remains controversial. This study presents a case report of a patient with Parkinson's disease who experienced rapid vertebral fracture and spinal cord compression after pedicle screw removal. We outlined the patient's management, and follow up and discuss consideration for screw removal.Case presentationA 58-year-old woman with an 8-year history of Parkinson's disease underwent lumbar surgery (L4-L5 oblique lumbar interbody fusion, L5-S1 transverse lumbar interbody fusion, and T12-L4 posterolateral lumbar fusion), including pedicle screw implantation at a local hospital 3 years prior for degenerative lumbar spondylolisthesis and lumbar spinal stenosis. She presented with lower back pain and bilateral lower limb numbness for 7 months. The patient was diagnosed with failed back surgery syndrome and underwent posterior fixation removal, interbody fusion cage removal, decompression, fusion with bone grafting, and new internal fixation (L4-S2). However, 3 months postoperatively, the lower back pain recurred and worsened by the fourth month, accompanied by lower limb weakness. Subsequently, the patient was diagnosed with L2 and L3 vertebral fractures and spinal cord injury.ResultsWith appropriate treatment including total L2 laminectomy with decompression, intertransverse bone grafting, L2 vertebroplasty, pedicle screw-rod fixation (T11-S2), and T11 screw tract augmentation, the patient exhibited a satisfactory prognosis at the 2-year follow-up.